Cooperative hunting in a discrete predator–prey system II. (15th March 2019) - Chow, Yunshyong; Jang, Sophia R.-J.; Wang, Hua-Ming
ABSTRACT: We investigate a discrete-time predator–prey system with cooperative hunting in the predators proposed by Chow et al. by determining local stability of the interior steady states analytically in certain parameter regimes. The system can have either zero, one or two interior steady states. We provide criteria for the stability of interior steady states when the system has either one or two interior steady states. Numerical examples are presented to confirm our analytical findings. It is concluded that cooperative hunting of the predators can promote predator persistence but may also drive the predator to a sudden extinction.